A collaborative approach to enabling stratified cancer medicine in the UK. Issue 12 (December 2015) - Tuff-Lacey, Alice; Shaw, Emily; Cummings, Rebecca; Walker, Ian; Johnson, Peter W.M.
Highlights: Evidence-based sample preparation protocols are required. In-house validation, quality assurance and a range of analyses are essential. Provision of the clinical service needs to keep pace with technological advances. The collation of routinely recorded clinical data for research presents significant challenges. Clinical reporting of molecular analyses benefits from standardisation of reporting terminology. Abstract : Embedding stratified cancer medicine into the patient pathway will require adaptation of the diagnostic pathway to incorporate predictive molecular analysis, presenting challenges of accessing tumour samples of sufficient quality and quantity for analysis and ensuring the timeliness, accuracy, and clinical validity of results. In 2010, Cancer Research UK (CRUK), in partnership with AstraZeneca and Pfizer, set up the Stratified Medicine Programme (SMP1) to work collaboratively with a small number of hospital and genetics laboratories to demonstrate the feasibility of testing large volumes of samples, while working towards more standardised and efficient processes. By June 2013, 9010 patient samples had been sent for genetic testing and here we present an overview of our experience and the wealth of insights that have been generated into the complexities of attempting this transformation of National Health Service (NHS) care.